Do Promotions Make Consumers More Generous? The Impact of Price Promotions on Consumers’ Donation Behavior - Zhang, Kuangjie; Cai, Fengyan; Shi, Zhengyu (Journal of Marketing, 2021)
Despite growing concerns regarding the increasing consumerism related to promotions, this research documents a positive effect of price promotions on consumers’ donation behavior. Specifically, the authors propose that price promotions increase consumers’ perceived resources, which in turn increase consumers’ donation behavior. A series of seven studies, combining field and experimental data, provide converging support for this proposition and its underlying mechanism of perceived resources. Furthermore, the authors show that the positive effect of price promotions on consumers’ donation behavior is attenuated when consumers focus on the amount of money spent (rather than saved), when consumers feel they have overspent their budget, and when the monetary savings cannot be realized immediately. Finally, the authors show that this effect is stronger when donation solicitation occurs immediately after the price promotion (vs. after a delay). This research documents a novel behavioral consequence of price promotions and uncovers a mechanism by which price promotions can lead to positive social consequences and contribute to a better world.